Corporate Paternalism and the Problem of Harmful Products. Issue 2 (November 2014) - Benson, Peter
<x xml:space="preserve">Abstract</x> Withstanding the many important differences between tobacco and firearms, the goal of this article is to analyze a similar set of public relations strategies in these industries. The tobacco industry seeks to focus things on the family and uphold a behavioral and psychological model of risk management in the face of alternative public health, regulatory, and preventative approaches. My concern is with discourse analysis, and in exploring the motives, interests, and effects of corporate communications, I document a convergence in how the tobacco and firearms industries approach questions of responsibility and agency. These case studies permit a wider theorization of the dynamics of what Michel Foucault calls "problematization."